2015
DOI: 10.1016/j.cct.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Motivating first-time, group O blood donors to return: Rationale and design of a randomized controlled trial of a post-donation telephone interview

Abstract: First-time blood donors are essential to the US donor pool, providing nearly a third of all donations. Unfortunately, there are a wide variety of obstacles to repeat donation and new donors are extremely difficult to retain. Because each donor experiences a unique set of deterrents, we developed a post-donation interview based on motivational interview principles in order to flexibly address individual barriers. The primary aim of this randomized clinical trial is to examine retention of first-time, group O bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…These procedures were approved by the institutional review boards of Ohio University, New York Blood Center, and the University of Cincinnati. The study was registered with http://ClinicalTrials.gov (NCT02274064) and additional study detail is available from a published protocol …”
Section: Methodsmentioning
confidence: 99%
“…These procedures were approved by the institutional review boards of Ohio University, New York Blood Center, and the University of Cincinnati. The study was registered with http://ClinicalTrials.gov (NCT02274064) and additional study detail is available from a published protocol …”
Section: Methodsmentioning
confidence: 99%
“…The content was guided by a standardized script that encouraged donors to explore intrinsic and extrinsic motivations for giving blood, identify concerns or barriers to future donation, and engage in individualized problem solving to address any perceived concerns or barriers. In a subsequent study of first‐time donors, participation in the interview promoted larger decreases in donation‐related anxiety, larger increases in donation confidence and intention, and a shift toward more self‐determined (i.e., internal) motivation to donate . Further, donors with high internal motivation who completed the interview showed higher repeat donation rates in the following year …”
mentioning
confidence: 90%
“…Full details regarding the study design are provided in prior reports . Therefore, the following text briefly outlines the study design and provides novel information regarding the assessment of follow‐up donation attempts.…”
Section: Methodsmentioning
confidence: 99%
“…Results of this study demonstrated that, compared with a no‐contact control group, participants in the motivational interview group had a significantly higher rate of repeat donation attempts within a 12‐month follow‐up period (67 vs 44%). More recently, the psychological effects of a motivational interview call were compared with a control phone call among participants who completed their first donation at New York Blood Center or Hoxworth Blood Center . Comparison of psychological measures administered approximately 3 weeks before and 1 week after the calls revealed that participation in the motivational interview was associated with significantly larger decreases in anxiety and significantly larger increases in confidence, intention, and internal motivation to donate blood relative to controls.…”
mentioning
confidence: 99%